The trauma of peer victimization: Psychophysiological and emotional characteristics of memory imagery in subjects with social anxiety disorder. (17th July 2014) - Sansen, Lisa M.; Iffland, Benjamin; Neuner, Frank
Abstract The study investigated the role of an associative information network as a mechanism underlying the relation of peer victimization and social anxiety disorder (SAD). A sample of N = 80 was divided according to diagnosis (SAD vs. no diagnosis) and amount of peer victimization (low vs. high). Responses to memory of a personally experienced aversive social situation and to imagining a standardized negative social situation were assessed. In terms of skin conductance level, subjects with SAD and peer victimization were more reactive to the memory script than the other three groups while responses to the standardized script did not vary. As to heart rate, there were no differences between the groups. Emotional responses presented with an inconsistent pattern. The results provide a first indication that associative memory structures resulting from aversive social experiences might play a role in the development and maintenance of SAD, but further research is needed.